Knowledge, perception, and antibiotic prescribing practice in the intensive care unit: Findings from the Malaysian public setting - Rozali, Mohammad Azrai; Ab Rahman, Norny Syafinaz; Sulaiman, Helmi; Abd Rahman, Nurul Azrin; Atiya, Nadia; Wan Mat, Wan Rahiza; Jamaluddin, Mohd Fadhil; Mazlan, Mohd Zulfakar; Mat Nor, Mohd Basri; Hasan, Mohd Shahnaz; Abdul-Aziz, Mohd Hafiz (Wolters-Kluwer, 2020)
Introduction: Approach to managing infection in the intensive care unit (ICU) often varies between institutions and not many readily adapt to available local guidelines despite it was constructed to suite local clinical scenario. Malaysia already has two published guidelines on managing infection in the ICU but data on its compliance are largely unknown. Objectives: A cross-sectional survey was carried out and sent to a total of 868 specialists working primarily in the ICU. The aim of this study was to explore knowledge, perception, and the antibiotic prescribing practice among specialists and advanced trainees in Malaysian ICU. Materials and Methods: A cross-sectional survey was used, consisted of three sections: knowledge, perception, and antibiotic prescribing practice in ICU. Three case vignettes on hospital-acquired pneumonia (HAP), infected necrotizing pancreatitis (INP), and catheter-related bloodstream infection (CRBSI) were used to explore antibiotic prescribing practice. Results: A total of 868 eligible subjects were approached with 104 responded to the survey. Three hundred eighty-nine antibiotics were chosen from seven different classes in the case vignettes. All respondents acknowledged the importance of pharmacokinetic/pharmacodynamic (PK/PD) in antibiotic optimization and majority (97.2%) perceived that current dosing is inadequate to achieve optimal PK/PD target in ICU patients. Majority (85.6%) believed that antibiotic dose should be streamlined to the organisms’ minimum inhibitory concentration (MIC). In terms of knowledge, only 64.4% provided the correct correlations between antibiotics and their respective PK/PD targets. Compliance rates in terms of antibiotic choices were at 79.8%, 77.8%, and 27.9% for HAI, INP, and CRBSI, respectively. Conclusion: Malaysian physicians are receptive to use PK/ PD approach to optimize antibiotic dosing in ICU patients. Nonetheless, there are still gaps in the knowledge of antibiotic PK/PD as well as its application in the critically ill, especially for β-lactams.